Environmental associated emotional distress and the dangers of climate change for pastoralist mental health - Cooper, Sarah; Hutchings, Paul; Butterworth, John A.; Joseph, Solome; Kebede, Abinet; Parker, Alison; Terefe, Bethel; Van Koppen, Barbara (Elsevier, 2019)
Pastoralists in the Horn of Africa are among the most vulnerable populations to climate change yet little is known about how environmental change shapes their wellbeing and mental health. This paper presents a formative study into the relations between emotion, wellbeing and water security among pastoralist communities in Afar, Ethiopia. It uses focus group and interview data to demonstrate the close relationship between environmental conditions and emotional wellbeing, and shows how current water insecurity leads to extreme worry and fatigue among the studied population, especially in the dry season. In the context of difficulties of translating mental health clinical classifications and diagnostic tools in cross-cultural settings, the paper argues the inductive study of emotion may be a useful approach for studying environmental determined wellbeing outcomes among marginal populations in the light of understanding climate change impacts.
Keywords: Environmental change; Wellbeing; Mental health; Pastoralists; Ethiopia